CALCULATION OF UNIT COST WITH TRADITIONAL METHOD AND ACTIVITY BASED COSTING METHOD; CASE STUDY OF DEPOK HEMODIALYSIS CLINIC. - supriadi supriadi (Jurnal Administrasi Bisnis Terapan, 2019)
AbstractThe purpose of the study is to compare the unit cost calculation method between the Activity Based Costing (ABC) method and the Traditional method. The object used is Hemodialysis (HD) service in a Hemodialysis Clinic in Depok, West Java. This research is a descriptive study, where the data used is secondary data from financial and non-financial records during January 2018 to December 2018 from the HD Clinic. This data is processed to determine the HD service unit costs using 2 methods namely the ABC and Traditional methods. The results of unit cost calculations using 2 methods do not make a difference. Suggestions for calculating HD service unit costs at HD clinics that do not have other services can use one of the two unit cost calculation methodsKeyword. Activity Based Costing, Unit Cost, Hemodialysis